(untitled) (Journal of the College of Languages (JCL), 2009)
This research has discussed the origins of ESP, addressed key notions about ESP and examined issues in ESP syllabus design. The content of the paper was determined by a need identified based on my experience as an ESL instructor designing and delivering the content-based language program - Language Preparation for the Cadets and Employment in the Iraqi College of Police . These issues, where possible, have been supported by current and pertinent academic literature. It is my sincerest hope that these observations will lend insight into the challenges facing the ESL instructor acting as ESP syllabus developer.